Effects of developmental and acquired disorders of the cornea on visual processes in children - Grałek, Mirosława; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
The paper discusses the role of the cornea in children’s visual processes. It highlights the most common causes, both congenital and acquired, that alter the corneal structure, impairing or entirely preventing its proper function. Congenital and acquired abnormalities of the cornea, particularly in its central part, can disrupt the normal development of vision, reduce visual acuity, or lead to vision loss. This impedes the formation of accurate stereoscopic vision. Children suspected of having corneal changes require early ophthalmological examination, including diagnostic tests and subsequent treatment. In some cases of acquired corneal disorders, causal treatment is possible. The cornea also plays a crucial role as a protective barrier for the anterior part of the eye.